A Rare Case of Pleural Tuberculosis with Tuberculous Pyomyositis - Lubis, Perdana Putra; Nugroho, Gilang Muhammad Setyo (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: Tuberculosis (TB) gained recognition throughout the 19th century as it inflicted significant mortality rates upon a vast number of individuals across the globe. Pleural tuberculosis and tuberculous pyomyositis are infrequently documented extra-pulmonary manifestations, with limited coverage in the medical literature, and their underlying pathophysiological mechanisms remain unclear. There is a scarcity of published evidence about the management of pleural tuberculosis with tuberculous pyomyositis. Case report: We reported a case of a 51-year-old female patient who presented with progressive exacerbation of dyspnea, elevated body temperature, nocturnal diaphoresis, active cough, and pleuritic chest discomfort localized to the right side for twelve weeks duration. This patient also had multiple bulges in the left lumbal, left upper chest, and axillary regions. Several people living near the patient’s home were diagnosed with tuberculosis. During the examination, the patient exhibited decreased breath sounds and a dull percussion note in the right lung field. The chest radiograph revealed a substantial pleural effusion in the right hemithorax. She was subsequently started on four daily anti-tuberculosis therapy and pleural fluid drainage. On the fifth month of follow-up, the patient showed improvement in symptoms and the bulging has reduced in size. Discussion: Pyomyositis is a suppurative infection of skeletal muscle that typically arises from the dissemination of pathogens through the bloodstream. The infection is commonly observed in tropical regions among persons who have significant underlying comorbidities or are immunocompromised. Conclusion: Pleural tuberculosis accompanied by tuberculous pyomyositis is an uncommon manifestation outside of the lungs, nevertheless, it is crucial to maintain vigilance regarding this condition. The timely identification of a disease is crucial for the implementation of appropriate treatment and subsequent resolution